Exploring mental toughness in soccer players of different levels of performance - Guillén Garcia, F.; Santana, J. (Revista Iberoamericana de Psicologia del Ejercicio y el Deporte, 2018)
The objective of the present study was to assess mental toughness in two groups of soccer players of different levels of performance. The participants included 242 male soccer players, ranging from 14 to 19 years of age who participated in official competitions for under 16s and under 19s. The Mental Toughness Index (MTI) was used and they were asked three questions related to their perception of their capacity to reach higher levels. Results show significant differences between under 16 players and under 19 players. Some differences were also observed between players of UD Las Palmas and the other teams. Overall, results appear to indicate that from an early age, some differences in regard to mental toughness can be found depending on the level of performance. This study provides data of very young athletes and uses an instrument which had never been used on Spanish soccer players. Further research in this field would be interesting, focusing on younger subjects and other individual and team sports.